An Analysis of the Effect of Social Media Marketing on the TikTok App on Purchase Intention, with Brand Awareness and Consumer Brand Engagement as Mediating Variables (A Study of Potential Consumers of Gatsby Perfume Products in Semarang) - Fariq Wildan Arkananta; Widya Prananta (Journal of Social Research, 2026)
The rapid growth of digital technology and TikTok usage has transformed marketing communication and consumer behavior, particularly in the fragrance industry. Gatsby perfume faces increasingly competitive market conditions and fluctuating brand performance, making it important to examine how TikTok-based social media marketing shapes consumer purchase intention. This study aims to analyze the effect of social media marketing on purchase intention, with brand awareness and consumer brand engagement as mediating variables among potential consumers of Gatsby perfume products in Semarang. This research employed a quantitative explanatory approach using a survey method. Data were collected from 120 respondents selected through purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 4.0. The findings show that social media marketing has a positive and significant effect on purchase intention, brand awareness, and consumer brand engagement. Brand awareness and consumer brand engagement also positively and significantly influence purchase intention. Furthermore, consumer brand engagement significantly mediates the relationship between social media marketing and purchase intention, while brand awareness does not significantly mediate this relationship. These results indicate that interactive, informative, personalized, and trend-based TikTok marketing can strengthen consumer engagement and encourage purchase intention. Therefore, Gatsby should prioritize engagement-oriented digital campaigns to enhance consumer interest and brand competitiveness